2015
DOI: 10.1021/jacs.5b04351
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Properties of Solid-State Structural Isomers: Ordered Intergrowths of SnSe and MoSe2

Abstract: A family of structural isomers [(SnSe)1.05]m(MoSe2)n were prepared using the modulated elemental reactant method by varying the layer sequence and layer thicknesses in the precursor. By varying the sequence of Sn-Se and Mo-Se layer pairs deposited and annealing the precursors to self-assemble the targeted compound, all six possible isomers [(SnSe)1.05]4(MoSe2)4, [(SnSe)1.05]3(MoSe2)3[(SnSe)1.05]1(MoSe2)1, [(SnSe)1.05]3(MoSe2)2[(SnSe)1.05]1(MoSe2)2, [(SnSe)1.05]2(MoSe2)3[(SnSe)1.05]2(MoSe2)1, [(SnSe)1.05]2(MoSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…These values are well below the calculated minimum thermal conductivities for the PbSe, SnSe, MoSe 2 , or WSe 2 constituents, and also significantly lower than the values measured thus far for crystalline misfit layered compounds. Interestingly, the thermal conductivity values are higher than those obtained for turbostratically disordered WSe 2 alone, and found to be essentially independent of the MX‐TX 2 interface density, a result which is in stark contrast to conventional semiconducting superlattices. The in‐plane thermal conductivity of free standing [(PbSe) 1+δ ] m [WSe 2 ] m films was found to be significantly higher than the cross‐plane values but still very low (∼ 0.4 W/m‐K) and nearly temperature independent .…”
Section: Unconventional Crystals: Quasicrystals Incommensurately Modmentioning
confidence: 64%
See 1 more Smart Citation
“…These values are well below the calculated minimum thermal conductivities for the PbSe, SnSe, MoSe 2 , or WSe 2 constituents, and also significantly lower than the values measured thus far for crystalline misfit layered compounds. Interestingly, the thermal conductivity values are higher than those obtained for turbostratically disordered WSe 2 alone, and found to be essentially independent of the MX‐TX 2 interface density, a result which is in stark contrast to conventional semiconducting superlattices. The in‐plane thermal conductivity of free standing [(PbSe) 1+δ ] m [WSe 2 ] m films was found to be significantly higher than the cross‐plane values but still very low (∼ 0.4 W/m‐K) and nearly temperature independent .…”
Section: Unconventional Crystals: Quasicrystals Incommensurately Modmentioning
confidence: 64%
“…The cross‐plane thermal conductivity of semiconducting [(MSe) 1+δ ] m [TSe 2 ] n thin films with M = Pb or Sn, T = Mo or W, and 1 ≤ m, n ≤ 5 has been measured by time domain thermoreflectance, revealing ultralow values between approximately 0.06 W/m‐K and 0.2 W/m‐K . These values are well below the calculated minimum thermal conductivities for the PbSe, SnSe, MoSe 2 , or WSe 2 constituents, and also significantly lower than the values measured thus far for crystalline misfit layered compounds.…”
Section: Unconventional Crystals: Quasicrystals Incommensurately Modmentioning
confidence: 87%
“…This material system consists of disordered layered basal plane crystals and exhibits κ values less than 0.1 W m −1 K −1 , which is attributed to strongly localized lattice vibrations. [ 14–18 ] There were also computational efforts with ab initio calculations to quantify the heat conduction across the interfaces, and the results indicated that the boundary conductance enhances with increasing interface density. [ 19 ]…”
Section: Figurementioning
confidence: 99%
“…While thermodynamically stable misfit layer compounds can be prepared typically only when n = m = 1, ferecrystals can be synthesized with a wide range of m and n values . One can even prepare ferecrystals that are structural isomers, only distinguishable from one another by the number of interfaces between the different building blocks …”
Section: Introductionmentioning
confidence: 99%